THE EFFECT OF SCHOOL CLIMATE, TRANSFORMATIONAL LEADERSHIP AND CO-CURRICULAR ACTIVITIES TOWARDS ACADEMIC PERFORMANCE IN SABAH MISSION SCHOOLS - Ganesan Kumarasamy; Veera Pandiyan Kaliani Sundram (International Journal of Accounting, Finance and Business, 2023)
The purpose of this study is to look at the elements that influence Form Five students' academic performance at mission schools in Sabah. The average grade score of SPM scores was used to measure academic attainment. The empirical data were collected through survey. Two mission schools with a total of 80 teachers were chosen using convenience sampling. The association between academic achievement, school category, and student characteristics were investigated using multiple regression analysis. In the form of linear terms and interaction terms, the demographic profile of instructors and school data about the overall percentage of students from each school were examined. Through multiple regression, independent variables such as school climate, transformational leadership, and co-curricular activities were found to have a significant impact on the outcome of the students’ academic performance.The study has determined the variables affecting students' academic performance in Sabah's mission secondary schools. The study's findings were important because they would help the educational institutions encourage the implementation of policies that would improve secondary school pupils' academic performance. In order to preserve academic achievement, the findings also show the necessity and practicality of applying the effective practises used in mission schools in educational institutions. To our best knowledge, this paper is one of the first to address the determinants of academic performance at mission schools in Sabah.